Evaluasi Kesiapan Sekolah dan Guru dalam Mengimplementasikan Kurikulum Merdeka: Tantangan dan Peluang di Tingkat SD - Lisa Oktavia; Ryan Hidayat (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to evaluate the readiness of schools and teacher in implementing the Merdeka Curriculum at the elementaru school llevel in Indonesia. Using a descriptive qualitative approach, data were obtained from literature review and content analysis. The findings indicate variations in the implementation of the Merdeka Curriculum across provinces, with some provinces achieving a hgh lebel of implementation. Factors such as the number of motivated teachers, local goverment support,and community involvement influence the success of implemetation. Recommendations for further actions include strengthening teacher training, expanding implementation, and empowering motivated teachers as steps to enhance the quality of education through the Merdeka Curriculum.